Microbiologia, composizione chimica e valori nutrizionali di prodotti ittici dei laghi lombardi - M.A. Paleari; G. Beretta; S. Pirani; V.M. Moretti (Chiriotti, 2009)
Different kinds of lake fish processed using different technologies: salting, smoking, pickling in vinegar, and marinating were considered. The products were obtained by processing some typical fishes from Lombardy lakes: Danube roach (Rutilus pigus), Landlocked shad (Alosa fallax lacustris), Common whitefish (Coregonus lavaretus), Artic char (Salvelinus alpinus), Italian bleak (Alburnus alborella), and derived eggs and botargo. Microbiological, chemical and gas-chromatographic analyses to determine the fatty acid profile were carried out. The microbiological results showed a safe situation due to the low microbiological charges present in the products. The proximate composition, the nutritional value and the fatty acid profile characterized by the presence of high unsaturated fatty acids demonstrated the importance of the fishery lake products and their processed derivates.